2019
DOI: 10.1007/978-3-030-24907-6_33
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Application-Layer Tunnels with Rules and Machine Learning

Abstract: Application-layer tunnels are often used to construct covert channels in order to transmit secret data, which is often applied to raise network threats in recent years. Detection of application-layer tunnels can assist identifying a variety of network threats, thus has high research significance. In this paper, we explore application-layer tunnel detection and propose a generic detection method by applying both rules and machine learning. Our detection method mainly consists of two parts: rule-based domain nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Specifically, it is a process to let computer systems or machines see, know, learn and predict the world like a human being. "Machine learning is the study of making machines acquire new knowledge, new skills, and reorganize existing knowledge" [70,[72][73][74]. At the beginning of the birth of machine learning, people performed researches to let a machine study, gain skills and build its own knowledge world automatically.…”
Section: Machine Learningmentioning
confidence: 99%
“…Specifically, it is a process to let computer systems or machines see, know, learn and predict the world like a human being. "Machine learning is the study of making machines acquire new knowledge, new skills, and reorganize existing knowledge" [70,[72][73][74]. At the beginning of the birth of machine learning, people performed researches to let a machine study, gain skills and build its own knowledge world automatically.…”
Section: Machine Learningmentioning
confidence: 99%
“…In the detection method based on statistical behavior, [18] counted 12 behavioral characteristics of covert tunnels by analyzing data characteristic information such as packet size, tunnel traffic type, and fixed format of data, and established an SVM machine learning model to detect covert tunnels. In [19], authors established an information entropy-based detection model by calculating the confusion level of the data portion of ICMP.…”
Section: Preliminariesmentioning
confidence: 99%
“…Some commercial software constructs feature databases by directly querying the feature signature of malware [6]. In [18], the feature databases were constructed by directly cutting words. In our paper, we found that ICMP covert tunnel traffic has obvious and specific attack intentions in the data part, such as SHELL_ATTACKS, ACCESS_SENSITIVE_DIRS, etc.…”
Section: Feature Database Constructionmentioning
confidence: 99%
“…Latest techniques include ML based techniques for filtering anomalous domain names. For example, in (Lin, 2019), they combine both techniques to enhace detection. However, DGA techniques keep evolving, creating more sophisticated DGAs, such as the dictionary-based ones.…”
Section: Motivation and Contributionsmentioning
confidence: 99%